Survival and Acidification Potential of Lactobacillus Plantarum MNC 21 Stored in Air-Dried Sorghum Flours - Yusuf Byenkya Byaruhanga; Stellah Byakika; Ivan Muzira Mukisa (University of Sultan Ageng Tirtayasa, 2022)
Increased commercialization of indigenous fermented foods requires availability of affordable starter cultures. The starters should also maintain functionality when stored at ambient conditions, especially where erratic power supply makes constant refrigeration unachievable. This study evaluated the survival of Lactobacillus plantarum MNC 21 starter culture air-dried (at 25 or 30°C) in sorghum flour and stored at 25°C for 30 days. Two sorghum varieties (malted and un-malted) were used. To determine their fermentation efficiency during storage, sterile sorghum malt slurries were inoculated with the dried culture and fermented at 30°C for 24 h. Acidification potential was determined at 5 days intervals by measuring microbial counts, pH and titratable acidity. Microbial concentrations dropped from 8-9 log cfu/g on day 0 to 1 log cfu/g on day 30. Sorghum variety and whether it was malted or un-malted did not affect culture survival. Culture dried at 25°C had better survival during the first 10 days (8-9 log cfu/g) than that dried at 30°C (8 log cfu/g) but survival between days 20-30 was similar (1-4 log cfu/g). The acidification potential (ability to reduce pH to ≤4.5) decreased with storage time: 4 h (day 0), 24 h (day 15), > 24 h (day 20) to no acidification (days 25-30). Air drying of starter cultures in sorghum flours coupled with storage at ambient temperatures could be adopted as a short-term preservation method. This low-cost technology is suitable for processors in developing countries where maintenance of a cold chain is hampered by unreliable electricity supply.